Silk fibroin-magnetic hybrid composite electrospun fibers for tissue engineering applications - Brito-Pereira, R. (2018)
This manuscript reports on the fabrication of silk fibroin (SF)-based magnetic electrospun fiber composites as scaffolds for tissue engineering applications. The magnetic responsiveness of the SF composite fibers was achieved by the inclusion of cobalt ferrite (CoFe2O4) or magnetite (Fe3O4) nanoparticles prior to processing the fibers via electrospinning. The influence of the processing parameters, including type and amount of nanoparticles in the composite, on the mean fiber size and size distribution was studied. Whereas the average diameter of pristine SF fibers was of 294±53nm, the inclusion of 5% of CoFe2O4 and Fe3O4 nanoparticles led to a slight increase in the fiber diameter. Nevertheless, the fiber diameter decreased with the higher nanoparticles loading. Regarding the physico-chemical properties of the fibrous mats, it was observed that the degree of crystallinity dropped from 67% of the pristine SF mats to 37% for the SF composites. On the other hand, the onset degradation temperature of the SF electrospun was not significantly altered by inclusion of ferrite nanoparticles. It is shown that the magnetization saturation increased with the nanoparticle filler content for both compositions (CoFe2O4/SF and Fe3O4/SF). Neither the SF pristine fibers nor the SF composites were cytotoxic, indicating their suitability for tissue engineering applications.